Novel Disabled‐1‐expressing neurons identified in adult brain and spinal cord. (19th November 2013) - Abadesco, Autumn D.; Cilluffo, Marianne; Yvone, Griselda M.; Carpenter, Ellen M.; Howell, Brian W.; Phelps, Patricia E.
Abstract Components of the Reelin‐signaling pathway are highly expressed in embryos and regulate neuronal positioning, whereas these molecules are expressed at low levels in adults and modulate synaptic plasticity. Reelin binds to Apolipoprotein E receptor 2 and Very‐low‐density lipoprotein receptors, triggers the phosphorylation of Disabled‐1 (Dab1), and initiates downstream signaling. The expression of Dab1 marks neurons that potentially respond to Reelin, yet phosphorylated Dab1 is difficult to detect due to its rapid ubiquitination and degradation. Here we used adult mice with a lacZ gene inserted into the dab1 locus to first verify the coexpression of β‐galactosidase (β‐gal) in established Dab1‐immunoreactive neurons and then identify novel Dab1‐expressing neurons. Both cerebellar Purkinje cells and spinal sympathetic preganglionic neurons have coincident Dab1 protein and β‐gal expression in dab1lacZ/+ mice. Adult pyramidal neurons in cortical layers II–III and V are labeled with Dab1 and/or β‐gal and are inverted in the dab1lacZ/lacZ neocortex, but not in the somatosensory barrel fields. Novel Dab1 expression was identified in GABAergic medial septum/diagonal band projection neurons, cerebellar Golgi interneurons, and small neurons in the deep cerebellar nuclei. Adult somatic motor neurons also express Dab1 and show ventromedial positioning errors in dab1‐null mice. These findings suggest that: (i) Reelin regulates the somatosensory barrel cortex differently than other neocortical areas, (ii) most Dab1 medial septum/diagonal band neurons are probably GABAergic projection neurons, and (iii) positioning errors in adult mutant Dab1‐labeled neurons vary from subtle to extensive.